Fluctuating world of Marian Smoluchowski - Fuliński, Andrzej (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2017)
The main goal of this paper is to present the Marian Smoluchowski’s work on thermal and primordial fluctuations which are the main cause of Brownian motion and one of the first empirical evidences for molecular structure of matter.